Self-perceived oral health among adults in Northeastern Brazil - Vale, Edivania Barbosa do; Mendes, Antonio da Cruz Gouveia; Moreira, Rafael da Silveira (Revista de Saúde Pública, 2013)
OBJECTIVE: To identify self-perceived oral health in adults and associated variables. METHODS: The study involved primary data from the Brazilian Oral Health Survey (SBBrasil) 2010 with 2,456 adults aged 35 to 44 in the Northeastern Brazil. The dependent variable was self-perceived oral health and the independent variables were grouped into four blocks: demographic, predisposing/facilitation, oral health status and those related to self-perceived need for treatment. The Rao and Scott test was used to test the association between these variables. To test the effect of the independent variables on the outcome, a multinomial logistic regression model was used according to the hierarchical model, resulting in an analysis divided into two stages: simple analysis and hierarchical multiple regression analysis. RESULTS: Positive self-perception of oral health was observed in 37% of the participants. In the final model, the features directly associated with this perception were being white, having a household income exceeding R 500.00, owning goods number above the median, having more sound teeth, not experiencing bleeding, not requiring prosthesis, Oral Imparcts on Daily Performances = 0, not requiring treatment, having gone to the dentist less than 3 years ago. CONCLUSIONS: The results show that self-perceived oral health in adults living in the Northeast is directly associated with a multidimensional structure of factors. The poor economic conditions associated with poor clinical conditions impact heavily on this population’s self-perception of oral health.